Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (Applied Mathematics and Computer Science)

Ausgewählte Beiträge des GMA-Fachausschusses 5.14 - Hoffmann, F.; Hüllermeier, Eyke; Kroll, A. (Computational Intelligence Automatisierungstechnik)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Data Min. Knowledge Discovery)

Visualization of evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Rejoinder on "Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.- M.; Hüllermeier, Eyke (Neurocomputing)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

Protein Sub-Cellular Localization Prediction for Special compartments via Optimized Time Series Distances - Mernberger, M.; Moog, M.; Stork, S.; Zauner, S.; Maier, U.G.; Hüllermeier, Eyke (J. Bioinformatics and Computational Biology)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Machine Learning)

Preference-Based Reinforcement Learning: evolutionary direct policy search using a preference-based racing algorithm - Busa-Fekete, Robert; Szörényi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Dependent binary relevance models for multi-label classification - Montanés, E.; Senge, Robin; Barranquero, J.; Quevedo, J.R.; Del Coz, J.J.; Hüllermeier, Eyke (Pattern Recognition)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, Ammar; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Extended Graph-Based Models for Enhanced Similarity Search in Cavbase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Identification of Functionally Releated Enzymes by Learning to Rank Methods - Stock, M.; Fober, T.; Hüllermeier, Eyke; Glinca, S,; Klebe, G.; Pahikkala, T.; Airola, A.; De Baets, B.; Wageman, W. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Power model design for ICT systems – A generic approach - Beister, Frederic; Dräxler, Martin; Aelken, Jörg; Karl, Holger (Computer Communications)

Design of an Electrical Interferometer at 120 GHz for Contactless Permittivity Characterization - Wessel, Jan; Schmalz, Klaus; Cahill, Brian; Scheytt, Christoph (Elektrotechnisches Kolloquium)

Architectural Low-Power Design Using Transaction-Based System Modeling and Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))
Energy efficiency drives the development of more and more complex low-power designs. Based on dynamic power management techniques, multiple voltage islands as well as a huge amount of power states are specified that have to be tested carefully. In this context, low-power design should start at an early stage using state-of-the-art system-level modeling and simulation techniques. However, there is neither a programming language nor any modeling standard that reflects variable power together with its functional side effects in a well-suited abstract manner. To overcome this limitation, we present a modeling approach on top of SystemC TLM to capture low-power design characteristics at electronic system-level. We demonstrate the usability by means of an existing open-source low-power design. The experimental results show that appropriate TLM instrumentation cause only minimal simulation overhead, but offer sufficient details to identify common low-power design errors.

Switchable slow wave transmission line in 130 nm SiGe technology at 115 GHz for phase detection based biosensors - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik (Microwave Symposium (IMS), 2014 IEEE MTT-S International)
A 115 GHz slow wave transmission line intended for phase detection based integrated biosensors is presented. The structure was fabricated in a 130 nm SiGe process. It achieved the targeted overall phase shift of 1° at 115 GHz. Moreover, the phase can be adjusted by 16 switches using Heterojunction Bipolar (HBT) transistors leading to a phase resolution of 0.125°. The change in input and output matching over all configurations of the switches is not higher than 0.8 dB and the transmission S 21 varies with less than 0.7 dB. To the authors knowledge, it is the first switchable slow wave structure using microstrip transmission lines along with a bipolar switch circuitry. Moreover, the presented structure provides a very powerful solution for real-time digital read-outs in integrated biosensors, without need of additional signal processing steps.

A 7 GHz biosensor for permittivity change with enhanced sensitivity through phase compensation - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik; Cahill, Brian (European Microwave Conference (EuMC))
A calibration technique as well as measurement results for a 7 GHz Biosensor are presented. It is shown that the applied sensor structure can be calibrated by adjusting the phase of a sensing element's transmission S21. This is realized by slowing down the wave traveling a microstrip line serving as a reference in the differential sensor structure. The dielectric properties along with certain physical boundaries of an obstacle covering parts of the microstrip line evoke that effect. Measurements with an ethanol serious along with simulation results showed that sensitivity can be increased substantially with this calibration technique. A change of the real part of the sample's permittivity of 48 leads to a 18 MHz frequency shift.

Wireless 100 Gb/s: PHY layer Overview and Challenges in THz freqency band - Kraemer, Rolf; Wolf, Andreas; Scheytt, Christoph; Kallfass, Ingmar; KrishneGowda, Karthik (2014 IEEE 15th Annual IEEE Wireless and Microwave Technology Conference (WAMICON))
There is a continuous increase of bandwidth-demanding services such as ultra HDTV, 3D TV, etc. which will require data rates up to 100-400 Gb/s for short range wireless communication. This paper introduces a novel mixed-mode design where both analog and digital domain design is considered, which helps in the reduction of power consumption. Parallel Sequence Spread Spectrum (PSSS) is used for physical layer (PHY) baseband technology, which considerably alleviates both transmitter and receiver design.

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Scheytt, Christoph (Design and Verification Conference (DVCON EUROPE))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.

Verific-MM: Systematized Verification Metrics Generation with UCIS for Improved Automation on Verification Closure - Kuznik, Christoph; Müller, Wolfgang (Design, Automation and Test in Europe DATE, University Booth, Dresden)
Verific-MM is an approach to systematize and accelerate the coverage plan engineering as well as the verification environment’s (functional) metric code generation -- usually a time-consuming and error-prone task -- in particular by (i) improving automation via assisted model-based approaches, utilizing recent industry standards such as UCIS and (ii) a supporting methodology suitable for various target (functional coverage) languages (IEEE-1800 SystemVerilog, IEEE-1647 e, IEEE-1666 SystemC).

System-on-Chip Design für Funkfrequenzen oberhalb von 100 GHz-Herausforderungen und potenzielle Anwendungen - Scheytt, Christoph (Analog 2014,14. Fachtagung der Gesellschaft für Mikroelektronik, Mikrosystemtechnik und Feinwerktechnik des VDE und VDI)

A -Band Four-Element Butler Matrix in 0.13 µm SiGe BiCMOS Technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Scheytt, Christoph; Ellinger, Frank (IEEE JOURNAL OF SOLID-STATE CIRCUITS)

Safety Evaluation of Automotive Electronics Using Virtual Prototypes: State of the Art and Research Challenges - Oetjens, Jan-Hendrik; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Bannow, Nico; Brinkmann, Oliver; Burger, Andreas; Chaari, Moomen; Chakraborty, Samarjit; Drechsler, R.; Ecker, Wolfgang; Grüttner, Kim; et al. (Design Automation Conference (DAC))
Intelligent automotive electronics significantly improved driving safety in the last decades. With the increasing complexity of automotive systems, dependability of the electronic components themselves and of their interaction must be assured to avoid any risk to driving safety due to unexpected failures caused by internal or external faults. Additionally, Virtual Prototypes (VPs) have been accepted in many areas of system development processes in the automotive industry as platforms for SW development, verification, and design space exploration. We believe that VPs will significantly contribute to the analysis of safety conditions for automotive electronics. This paper shows the advantages of such a methodology based on today's industrial needs, presents the current state of the art in this field, and outlines upcoming research challenges that need to be addressed to make this vision a reality.

Real-time capable methods to determine the magnet temperature of permanent magnet synchronous motors—A review - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (IECON 2014-40th Annual Conference of the IEEE Industrial Electronics Society)

Determination of rotor temperature for an interior permanent magnet synchronous machine using a precise flux observer - Specht, Andreas; Wallscheid, Oliver; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014-ECCE ASIA))

Adaptable AC Input Phase Switching for Optimum Utilization of Various Grid Configurations supplying Power Electronic Converters and EV/HEV On Board Chargers - Schafmeister, Frank; Ide, Peter; Richter, Jörg (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A Soft-Switching Interleaved DC-DC Converter with Integrated Magnetics for High Voltage Battery Charger - Li, Ronggyuan; Njiende, Hugues; Schafmeister, Frank; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Resistorless Precharging of Boost PFCs by Phase Angle Control of Thyristors - Schafmeister, Frank; Hufnagel, Michael; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Discrete-time design of adaptive current controller for interior permanent magnet synchronous motors (IPMSM) with high magnetic saturation - Peters, Wilhelm; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Monitoring critical temperatures in permanent magnet synchronous motors using low-order thermal models - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Real-time implementation of an online Model Predictive Control for IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Efficiency-optimized Model Predictive Torque Control for IPMSM - Leuer, Michael; Ruting, Arne; Böcker, Joachim (2014 IEEE International Energy Conference (ENERGYCON))

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Power profile based selection and operation optimization of parallel-connected power converter combinations - Vogt, T.; Peters, A.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Voltage sequence control based high-current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (2014 IEEE Energy Conversion Congress and Exposition (ECCE))

A completely modular power converter for high-power high-current DC applications - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Ermittlung der Rotortemperatur einer Synchronmaschine mit eingebetteten Permanentmagneten für einen automobilen Traktionsantrieb mittels Beobachter basierend auf elektrischen Größen - Specht, A.

Model-Based Development of DC-DC Converters with Wide Operation Range and High Dynamics - Cao, Z.

Modeling Optimization and Control Design for LCC Resonant Converter Applied in Very Low Frequency High Voltage Generator - Hu, M.

Wirkungsgradoptimale Regelung eines elektrischen Fahrantriebes mit variabler Zwischenkreisspannung - Pohlenz, Daniel

Digital Control for Interleaved Boost Power Factor Correction (PFC) Rectifiers - Grote, T.

Modellprädiktive Regelung permanent erregter Synchronmotoren im Antriebsstrang von Automobilen - Leuer, M.

Evaluierung und Anwendung eines Emulators für elektrische Maschinen in der Entwicklung von Elektro- und Hybridfahrzeugen - Uebener, S.

Traktionsantrieb mit linearem geschalteten Reluktanzmotor für ein autonomes Bahnfahrzeug - Schneider, T.

Comparison of Hot Spot Investigations under Laboratory and Field Conditions at Photovoltaic Modules - Wendlandt, Stefan; Krause, Melanie; Berendes, Sarah; Hanusch, Matthias; Drobisch, Alexander; Berghold, Juliane; Schoppa, Michael; Grunow, Paul; Krauter, Stefan (Proceedings of the 29th European Photovoltaic Solar Energy Conference and Exhibition, Amsterdam (The Netherlands), September 22-16, 2014)

Variational formulation and structure-preserving discretization of nonlinear electric circuits - Ober-Blöbaum, Sina; Lindhorst, H. (21st International Symposium on Mathematical Theory of Networks and Systems)

On the role of quadrature rules and system dimensions in variational multirate integrators - Gail, T.; Leyendecker, S.; Ober-Blöbaum, Sina (3rd Joint Interntaional Conference on Multibody System Dynamics)

Case Study - Trächtler, Ansgar; Kleinjohann, Bernd; Heinzemann, Christian; Rasche, Christoph; Priesterjahn, Claudia; Steenken, Dominik; Wehrheim, Heike; Gausemeier, Jürgen; Flaßkamp, Kathrin; Kleinjohann, Lisa; Krüger, Martin; Iwanek, Peter; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Construction and analysis of higher order Galerkin variational integrators - Ober-Blöbaum, Sina; Saake, N. (Advances in Computational Mathematics)

Methods for the Design and Development - Anacker, H.; Dellnitz, M.; Flaßkamp, K.; Grocsbrink, S.; Hartmann, P.; Heinzemann, C.; Horenkamp, C.; Kleinjohann, B.; Korf, S.; Krüger, M.; Müller, W.; Ober-Blöbaum, Sina; et al. (Jürgen Gausemeier, Franz Josef Rammig, and Wilhelm Schäfer, editors, Design Methodology for Intelligent Technical Systems)

Dependability of Self-optimizing Mechatronic Systems - Dangelmeier, W.; Dellnitz, M.; Dorociak, R.; Flaßkamp, K.; Gausemeier, J.; Groesbrink, S.; Hartmann, P.; Heinzemann, C.; Hölscher, C.; Iwanek, P.; Keßler, J.H.; Kleinjohann, B.; et al. (Lecture Notes in Mechanical Engineering)

The paradigm of self-optimization - Dellnitz, M.; Dumitrescu, R.; Flaßkamp, K.; Gausemeier, J.; Hartmann, P.; Iwanek, P.; Korf, S.; Krüger, M.; Ober-Blöbaum, Sina; Porrmann, M.; Priesterjahn, C.; Stahl, K.; et al. (Jürgen Gausemeier, Franz Josef Rammig, and Wilhelm Schäfer, editors, Design Methodology for Intelligent Technical Systems)

Variational Lie group formulation of geometrically exact beam dynamics: Synchronous and asynchronous integration - Leitz, T.; Ober-Blöbaum, Sina; Leyendecker, S. (Zdravko Terze, Multibody Dynamics)

Equivariant spectral asymptotics forh-pseudodifferential operators - Weich, Tobias (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Die Rolle von Batteriespeichern in KMU-Microgrids - Vogt, T.; Böcker, Joachim; Kempen, S. (BWK – Das Energie-Fachmagazin – Springer VDI Verlag, Ausgabe 12-2014)

Design Considerations on Peak Power Clipping Thresholds in Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (6th World Conference on Photovoltaic Energy Conversion (WCPEC))

Exponential ergodicity of killed Lévy processes in a finite interval - Kolb, Martin; Savov, Mladen (Electronic Communications in Probability)
Following Bertoin who considered the ergodicity and exponential decay of Lévy processes in a finite domain, we consider general Lévy processes and their ergodicity and exponential decay in a finite interval. More precisely, given Ta=inf{t>0:Xt∉. Under general conditions, e.g. absolute continuity of the transition semigroup of the unkilled Lévy process, we prove that the killed semigroup is a compact operator. Thus, we prove stronger results in view of the exponential ergodicity and estimates of the speed of convergence. Our results are presented in a Lévy processes setting but are well applicable for Markov processes in a finite interval under information about Lebesgue irreducibility of the killed semigroup and that the killed process is a double Feller process. For example, this scheme is applicable to a work of Pistorius.

The Brownian traveller on manifolds - Kolb, Martin; Krejčiřík, David (Journal of Spectral Theory)
We study the influence of the intrinsic curvature on the large time behaviour of the heat equation in a tubular neighbourhood of an unbounded geodesic in a two-dimensional Riemannian manifold. Since we consider killing boundary conditions, there is always an exponential-type decay for the heat semigroup. We show that this exponential-type decay is slower for positively curved manifolds comparing to the flat case. As the main result, we establish a sharp extra polynomial-type decay for the heat semigroup on negatively curved manifolds comparing to the flat case. The proof employs the existence of Hardy-type inequalities for the Dirichlet Laplacian in the tubular neighbourhoods on negatively curved manifolds and the method of self-similar variables and weighted Sobolev spaces for the heat equation.

mm-Wellen- und Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Fakultätskolloquium der Fakultät für Elektrotechnik und Informationstechnik)

Architectural Low-Power Design Using Transaction-Based System Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))

Source code annotated memory leak detection for soft real time embedded systems with resource constraints - Joy, M. tech. Mabel Mary; Müller, Wolfgang; Rammig, Franz-Josef (12th IEEE International conference on Embedded Computing)

Advanced SoC Virtual Prototyping for System-Level Power Planning and Validation - Mischkalla, Fabian; Müller, Wolfgang (PATMOS 2014)

Fault Effect Modeling in a Heterogeneous SystemC Based Virtual Platform Framework for Cyber Physical Systems - Becker, Markus; Kuznik, Christoph; Müller, Wolfgang
This paper presents an advanced eight levels spanning SystemC based virtual platform methodology and framework - referred to as HeroeS 3 - providing smooth application to platform mapping and continuous co-refinement of a virtual prototype with its physical environment model. For heterogeneity support, various SystemC extensions are combined covering continuous/discrete models of computation and different communication abstractions, such as analog mixed-signal models, abstract RTOS/HAL/middleware models, TLM bus models, and QEMU wrappers. We enable dependability assessment by Fault Effect Modeling (FEM) at the virtual prototype in order to avoid risking physical injury or damage. Also, simulation results are deterministic and can be evaluated interactively or offline. We apply FEM to both the physical environment model and the different abstractions of the virtual prototype. Currently, we focus on sensor failures and application control flow errors.
Keywords: Computational modeling; Finite element analysis; Prototypes; Abstracts; Software; Fault tolerance; Fault tolerant systems

An Assisted Single Source Verification Metric Model Code Generation Methodology - Kuznik, Christoph; Müller, Wolfgang; Defo, Gilles Bertrand
The ever-increasing complexity of heterogeneous electronic systems demand for intensified abstraction and automation efforts to improve design, verification and validation productivity, especially in earlier phases of system engineering. Within the verification activity various metrics can be applied to determine functional correctness or the overall progress. Here, a supporting verification methodology defining high-level verification planning down to the actual metric code development is essential. Moreover, an advanced assistance for the designer, such as a tooling infrastructure to automatize and accelerate the metric code implementation, is needed to minimize the influence of errorprone manual coding. In this article we present a single-source verification metric code-generation methodology for improved coverage automation. We determine (i) a suitable metric model for model-based capture of verification metrics as well as (ii) an assisted model-based processing and generation flow of the verification environment and metric skeletons. We apply our method to a SystemC case-study, in doing so, targeting metric code implementation productivity and consistency enhancement.
Keywords: System Design; Verification

Modellierung effizienter Stresstest-Umgebungen für virtuelle Prototypen mit SVM - Kuznik, Christoph; Müller, Wolfgang (26. ITG / GI / GMM Workshop Testmethoden und Zuverlässigkeit von Schaltungen und Systemen)
Zur Sicherstellung hoher Zuverlässigkeits- und Fehlertoleranzwerte von Schaltungen und ganzen Systemen finden vermehrt Test- und Verifikationsmethoden Anwendung die einen virtuellen Prototypen (VP) des Systems bereits frühzeitig im Entwurfsablauf einem Stresstest unterziehen. Hierbei werden speziell für die Domäne relevante Fehlerinjektoren verwendet (Digital, Mixed-Signal, Mechanik) die anhand von Fehlermodellen geeignete Testfälle erzeugen und in das System über Stimuli bzw. direkt injizieren. Jede effektive Anwendung einer Methode bedingt jedoch auch das Vorhandensein einer zugrundeliegenden Methodik. In diesem Beitrag wird die System Verification Methodology (SVM) vorgestellt werden, eine universell einsetzbare und erweiterbare Infrastruktur zur Beschreibung von Testumgebungen auf Basis der SystemC Sprache und Simulationskernels.

Semi-automatische Generierung von Überdeckungsmetriken mittels methodischer Verikationsplan Verarbeitung - Kuznik, Christoph; Defo, Bertrand Gilles; Müller, Wolfgang (17. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2014))

An Assisted Single Source Verification Metric Model Code Generation Methodology - Kuznik, Christoph; Defo, Bertrand Gilles; Müller, Wolfgang (Electronic System Level Synthesis Conference (ESLSyn))

Lecture meets laboratory experimental experiences for large audiences: Concept and implementation - Temmen, Katrin; Nofen, Barbara; Wehebrink, Markus (2014 IEEE Global Engineering Education Conference (EDUCON))

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Formation and interaction of resonance chains in the open three-disk system - Weich, Tobias; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)
Keywords: General Physics and Astronomy

PU-CMA-QAM BASED MIMO EQUALIZATION IN DSP-ENABLED PDM-16-QAM RECEIVERS - Panhwar, M. F.; Sandel, D.; Woerdehoff, C.; Puntsri, K.; Hussin, S.; Noé, Reinhold (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

Fiber nonlinearity Mitigation in CO-OFDM Systems using Dual Compensators - Hussin, S.; Noé, Reinhold (2014 IEEE PHOTONICS CONFERENCE (IPC))

REALTIME DIGITAL SIGNAL PROCESSING IN COHERENT OPTICAL PDM-QPSK AND PDM-16-QAM TRANSMISSION - Noé, Reinhold; Panhwar, M. F.; Woerdehoff, C.; Sandel, D. (2014 PROCEEDINGS OF THE 22ND EUROPEAN SIGNAL PROCESSING CONFERENCE (EUSIPCO))

SIMPLE POLARIZATION-DEPENDENT LOSS MEASUREMENT BASED ON POLARIZATION SCRAMBLING - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

Versatile endless optical polarization controller/tracker/demultiplexer - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali (OPTICS EXPRESS)

IMPROVEMENT OF RF-PILOT PHASE NOISE COMPENSATION FOR CO-OFDM TRANSMISSION SYSTEMS VIA COMMON PHASE ERROR EQUALIZER - Hussin, S.; Noé, Reinhold; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

40 dB CROSSTALK SUPPRESSION IN HIGH-PRECISION ENDLESS POLARIZATION CONTROL - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

APD-BASED INTERFERENCE DETECTORS YIELD 7-dB DYNAMIC RANGE OF 70-krad/s PDM-DPSK ENDLESS POLARIZATION DEMULTIPLEXER - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz Bandwidth of 70-krad/s Endless Optical Polarization Control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (2014 OPTICAL FIBER COMMUNICATIONS CONFERENCE AND EXHIBITION (OFC))

APD-BASED INTERFERENCE DETECTORS YIELD 7-dB DYNAMIC RANGE OF 70-krad/s PDM-DPSK ENDLESS POLARIZATION DEMULTIPLEXER - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

40 dB CROSSTALK SUPPRESSION IN HIGH-PRECISION ENDLESS POLARIZATION CONTROL - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz bandwidth of 70-krad/s endless optical polarization control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (OFC 2014)

Convolution algebras for Heckman–Opdam polynomials derived from compact Grassmannians - Rösler, Margit; Remling, Heiko (Journal of Approximation Theory)
Keywords: Applied Mathematics; General Mathematics; Numerical Analysis; Analysis

Design and Measurement Techniques for an 80 Gb/s 1-Tap Decision Feedback Equalizer - Awny, Ahmed; Möller, Lothar; Junio, Josef; Scheytt, Christoph; Thiede, Andreas (IEEE JOURNAL OF SOLID-STATE CIRCUITS)
A millimeter wave frequency mixed-signal design of a 1-tap half-rate look-ahead decision feedback equalizer for 80 Gb/s short-reach optical communication systems is presented. On-wafer tests are developed to determine the maximum operating bit rate of the equalizer. Results are also presented for intersymbol interference mitigation at 80 Gb/s for a 20 GHz bandwidth-limited channel. Further improvements on the architecture of the 80 Gb/s equalizer are discussed and used in the design and on-wafer measurement of a 110 Gb/s equalizer. The equalizers are designed in a 0.13 μm SiGe:C BiCMOS technology. The 80 and 110 Gb/s versions dissipate 4 and 5.75 W, respectively and occupy 2 and 2.56 mm 2 , respectively.

FIBER NONLINEARITY TOLERANCE OF PARTIAL PILOT FILLING IN CO-OFDM TRANSMISSION SYSTEMS - Hussin, S.; Noé, Reinhold; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz Bandwidth of 70-krad/s Endless Optical Polarization Control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (2014 OPTICAL FIBER COMMUNICATIONS CONFERENCE AND EXHIBITION (OFC))

Optimizing spatial filters for the extraction of envelope-coupled neural oscillations - Dähne, S.; Nikulin, V. V.; Ramírez, D.; Schreier, P. J.; Müller, K.-R.; Haufe, S. (Proc. Int. Work. Pattern Recognition In Neuroimaging)
Amplitude-to-amplitude interactions between neural oscillations are of a special interest as they show how the strength of spatial synchronization in different neuronal populations relates to each other during a given task. While, previously, amplitude-to-amplitude correlations were studied primarily on the sensor level, we present a source separation approach using spatial filters which maximize the correlation between the envelopes of brain oscillations recorded with electro-/magnetencephalography (EEG/MEG) or intracranial multichannel recordings. Our approach, which is called canonical source power correlation analysis (cSPoC), is thereby capable of extracting genuine brain oscillations solely based on their assumed coupling behavior even when the signal-to-noise ratio of the signals is low.

Testing blind separability of complex Gaussian mixtures - Ramírez, D.; Schreier, P. J.; Vía, J.; Santamaría, I. (Signal Process.)
The separation of a complex mixture based solely on second-order statistics can be achieved using the Strong Uncorrelating Transform (SUT) if and only if all sources have distinct circularity coefficients. However, in most problems we do not know the circularity coefficients, and they must be estimated from observed data. In this work, we propose a detector, based on the generalized likelihood ratio test (GLRT), to test the separability of a complex Gaussian mixture using the SUT. For the separable case (distinct circularity coefficients), the maximum likelihood (ML) estimates are straightforward. On the other hand, for the non-separable case (at least one circularity coefficient has multiplicity greater than one), the ML estimates are much more difficult to obtain. To set the threshold, we exploit Wilks’ theorem, which gives the asymptotic distribution of the GLRT under the null hypothesis. Finally, numerical simulations show the good performance of the proposed detector and the accuracy of Wilks’ approximation.

A Bayesian approach for adaptive multiantenna sensing in cognitive radio networks - Manco-Vásquez, J.; Lázaro-Gredilla, M.; Ramírez, D.; Vía, J.; Santamaría, I. (Signal Process.)

Optimum analog receive filters for detection and inference under a sampling rate constraint - Stein, Manuel; Lenz, Andreas; Mezghani, Amine; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Spatial Shaping and Precoding Design for Underlay MIMO Interference Channels - Lameiro, Christian; Utschick, Wolfgang; Santamaría, Ignacio (Proc. Int. ITG Work. Smart Antennas)

Information-preserving spatial filtering for direction-of-arrival estimation - Stein, Manuel; Castañeda, Mario; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Neue Anwendungsgebiete für Computer Assisted Surgery (CAS) - Schreier, Peter J. (ForschungsForum Paderborn)

Will the 1-bit GNSS receiver prevail? - Stein, Manuel; Nossek, Josef A. (Proc. of IEEE/ION PLANS 2014)

An asymptotic GLRT for the detection of cyclostationary signals - Ramírez, D.; Scharf, L. L.; Vía, J.; Santamaría, I.; Schreier, P. J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
We derive the generalized likelihood ratio test (GLRT) for detecting cyclostationarity in scalar-valued time series. The main idea behind our approach is Gladyshev’s relationship, which states that when the scalar-valued cyclostationary sig- nal is blocked at the known cycle period it produces a vector- valued wide-sense stationary process. This result amounts to saying that the covariance matrix of the vector obtained by stacking all observations of the time series is block-Toeplitz if the signal is cyclostationary, and Toeplitz if the signal is wide- sense stationary. The derivation of the GLRT requires the maximum likelihood estimates of Toeplitz and block-Toeplitz matrices. This can be managed asymptotically (for large num- berofsamples)exploitingSzego ̈’stheoremanditsgeneraliza- tion for vector-valued processes. Simulation results show the good performance of the proposed GLRT.